Niewydolność serca i płuc, transplantologiaHeart regeneration due to long-term mechanical circulatory support with the POLVAD pump – case report - Pacholewicz, Jerzy; Zakliczyński, Michał; Niklewski, Tomasz; Kubacki, Krzysztof; Kustosz, Roman; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
Aim: The aim of this study was to assess safety, feasibility and efficacy of the Polish Ventricular Assist Device (POLVAD) implanted in a patient with severe dilated cardiomyopathy as a bridge to recovery. Material and Methods: A 20-year-old male patient was admitted to the hospital in a life-threatening condition, haemodynamically unstable with symptoms of low output syndrome. An intra-aortic balloon pump was introduced together with inotropic support for more than two weeks without any clinical improvement. Echocardiogram revealed very poor left ventricular ejection fraction (10-15%) and severely dilated ventricle (LVEDD 6.9 cm LVEDV 220 ml). Based on the above-mentioned symptoms and findings an acute, toxic, severe dilated cardiomyopathy was diagnosed. Despite maximum medical therapy no improvement was observed; therefore the patient was qualified for heart support using the POLCAS system. On 01/08/2007 POLCAS was successfully implanted as a left ventricular support together with concomitant tricuspid valve annuloplasty. LV global and regional function was assessed twice weekly by transthoracic echocardiography. Results: The patient remained on VAD support for 151 days. There were no early or late complications such as bleeding, thromboembolic events, infection or mechanical pump dysfunction, allowing for immediate physical rehabilitation. After 5 months of LV support, due to significant improvement of the patient’s cardiac efficiency, including myocardial contractility with increase of left ventricular ejection fraction EF +35% and significant reduction of EDV=140 ml, LVEDD 5.5 cm, a decision to explant the POLVAD device was taken. Pharmacological treatment and rehabilitation were continued, and the patient’s cardiac competence was regained. The patient was discharged from the hospital in NYHA I class, with EF=-40 %. Conclusions: Mechanical circulatory support using a POLVAD blood pump for a period of 5 months in a 20-year-old patient with severe dilated cardiomyopathy led to myocardial regeneration and regression of heart failure symptoms.